Trainee Involvement in Transforaminal Epidural Steroid Injections Associated With Increased Incidence of Vasovagal Reactions. Issue 10 (19th April 2014) - Schneider, Byron; Kennedy, David J.; Casey, Ellen; Smuck, Matthew; Conrad, Bryan; Plastaras, Christopher
Abstract : Objectives: To evaluate whether trainee involvement (resident and fellow) during transforaminal epidural steroid injections (TFESI) results in greater rates of vasovagal reactions. Design: Retrospective study on consecutive patients. Setting: Single academic medical center with multiple attending physicians and trainees. Participants: A total of 2642 consecutive subjects undergoing 4482 TFESI were analyzed from March 8, 2004, to January 30, 2009. Main Outcome Measures: The Pearson χ 2 test was used to determine the relationship between vasovagal reactions and level of trainee involvement. Results: A total of 4482 TFESIs were performed, with 157 (3.5%) of procedures complicated by a vasovagal reaction. An attending physician performed 2884 (64.3%) procedures without trainee involvement, with only 79 (2.7%) vasovagal reaction noted. A fellow was involved in 723 (16.1%) procedures, with 30 (4.1%) noted to have a vasovagal reaction. A resident was involved in 875 (19.5%) procedures, with 48 (5.5%) having a vasovagal reaction. Overall, trainees were involved in 1598 (35.7%) cases, of which 78 (4.9%) were complicated by vasovagal reaction. When a trainee was involved in the case, there was a greater incidence of vasovagal episodes ( P < .001, χ 2 = 16.047). Although there was a trend towards greater vasovagal rates with residents over fellows, this did not reach statistical difference. Conclusions: Vasovagal reactions can occur with spine injection procedures and may result in premature procedure termination or other adverse events. Although this retrospective study has significant potential for bias, it appears that trainee involvement in a TFESI is associated with a greater incidence of vasovagal reaction ( P < .001, χ 2 = 16.047).